Analisis Seleksi dan Program Orientasi dalam Meningkatkan Adaptasi Karyawan Baru: Studi Literatur 2019-2024 - Natasya Risma Putri; Riza Nur Khikmiah; Mardiyah Mardiyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the relationship between the selection process and orientation programs in improving new employee adaptation and organizational performance. The method used is a Systematic Literature Review (SLR) by analyzing articles published in the period 2019–2024 through the Scopus, DOAJ, and Google Scholar databases. The synthesis results identified five main thematic categories, namely selection sources, selection objectives, types of acceptance tests, aspects of orientation programs, and employee adaptation outcomes. The findings show that competency-based selection, supported by the use of digital technology and structured assessments, can improve job fit accuracy and reduce the risk of turnover in the early stages of employment. In addition, comprehensive orientation programs that include organizational introduction, work culture socialization, technical mentoring, and social support have a significant impact on strengthening role clarity, psychological comfort, and early employee productivity. The literature review also revealed a number of challenges, such as selection bias, limited HR competencies, lack of transparency in placement and promotion, and suboptimal digital integration in HR processes. These challenges impact the organization's effectiveness in acquiring and integrating suitable talent. Overall, this study concludes that the integration of accurate selection processes and structured orientation programs is key to optimizing new employee adaptation and improving organizational performance in the digital era. Practical recommendations and directions for further research are also provided